Law Enforcement on Ownership of Business Identification Numbers Against Micro, Small and Medium Enterprises in Bukit Merapin Village - Nurfadillah, Zacky; aizin, Irawan F; Fahriansyah, Fahmi; Fadillah, M. Rizky; Hakim, Fauzan; Putri, Shindy Fretisya; Farihah, Najiatul (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2025)
This study aims to examine the legal enforcement of Business Identification Number (NIB) ownership among Micro, Small, and Medium Enterprises (MSMEs) in Bukit Merapin Urban Village. Although the government has introduced a risk-based licensing system through the Online Single Submission (OSS) platform, in practice, most business actors in the area still do not possess an NIB. This research adopts an empirical juridical approach with a descriptive qualitative method, supported by observations, interviews, and official data from relevant institutions. The findings reveal that the low rate of NIB ownership is primarily caused by limited legal literacy, insufficient access to digital technology, and the lack of active socialization by local government authorities. This situation highlights a gap between the normative framework of licensing regulation and the actual legal practice at the grassroots level. NIB should not merely be seen as an administrative requirement, but rather as a legal instrument that ensures protection and economic empowerment for small-scale entrepreneurs. Therefore, affirmative actions such as legal education, OSS technical assistance, and simplified licensing facilitation are urgently needed to promote administrative justice and equitable legal recognition for MSMEs.